Join the growing community of curious minds on IDNLearn.com. Discover in-depth and trustworthy answers to all your questions from our experienced community members.
Sagot :
Let's determine the [tex]$y$[/tex]-intercept and the horizontal asymptote for the function [tex]\( g(x) = 3^x + 4 \)[/tex].
### Finding the [tex]$y$[/tex]-intercept
The [tex]$y$[/tex]-intercept occurs where [tex]\( x = 0 \)[/tex]. To find the [tex]$y$[/tex]-intercept, evaluate [tex]\( g(x) \)[/tex] at [tex]\( x = 0 \)[/tex]:
[tex]\[ g(0) = 3^0 + 4 \][/tex]
Since [tex]\( 3^0 = 1 \)[/tex]:
[tex]\[ g(0) = 1 + 4 = 5 \][/tex]
Thus, the [tex]$y$[/tex]-intercept of the function is [tex]\( (0, 5) \)[/tex].
### Finding the horizontal asymptote
To determine the horizontal asymptote, we need to analyze the behavior of [tex]\( g(x) = 3^x + 4 \)[/tex] as [tex]\( x \)[/tex] approaches positive and negative infinity.
1. As [tex]\( x \)[/tex] approaches positive infinity ([tex]\( x \rightarrow \infty \)[/tex]):
- [tex]\( 3^x \)[/tex] becomes very large.
- [tex]\( g(x) = 3^x + 4 \)[/tex] will be dominated by the [tex]\( 3^x \)[/tex] term, and the function will go to infinity.
2. As [tex]\( x \)[/tex] approaches negative infinity ([tex]\( x \rightarrow -\infty \)[/tex]):
- [tex]\( 3^x \)[/tex] approaches 0 because any number raised to a negative power decreases towards zero.
- So, [tex]\( g(x) = 3^x + 4 \)[/tex] approaches [tex]\( 0 + 4 \)[/tex].
Hence, as [tex]\( x \)[/tex] approaches negative infinity, [tex]\( g(x) \)[/tex] approaches 4. Thus, the horizontal asymptote is:
[tex]\[ y = 4 \][/tex]
### Conclusion
The [tex]$y$[/tex]-intercept is [tex]\( (0, 5) \)[/tex] and the horizontal asymptote is [tex]\( y = 4 \)[/tex].
Thus, the correct multiple-choice answer is:
[tex]\[ (0, 5); y = 4 \][/tex]
### Finding the [tex]$y$[/tex]-intercept
The [tex]$y$[/tex]-intercept occurs where [tex]\( x = 0 \)[/tex]. To find the [tex]$y$[/tex]-intercept, evaluate [tex]\( g(x) \)[/tex] at [tex]\( x = 0 \)[/tex]:
[tex]\[ g(0) = 3^0 + 4 \][/tex]
Since [tex]\( 3^0 = 1 \)[/tex]:
[tex]\[ g(0) = 1 + 4 = 5 \][/tex]
Thus, the [tex]$y$[/tex]-intercept of the function is [tex]\( (0, 5) \)[/tex].
### Finding the horizontal asymptote
To determine the horizontal asymptote, we need to analyze the behavior of [tex]\( g(x) = 3^x + 4 \)[/tex] as [tex]\( x \)[/tex] approaches positive and negative infinity.
1. As [tex]\( x \)[/tex] approaches positive infinity ([tex]\( x \rightarrow \infty \)[/tex]):
- [tex]\( 3^x \)[/tex] becomes very large.
- [tex]\( g(x) = 3^x + 4 \)[/tex] will be dominated by the [tex]\( 3^x \)[/tex] term, and the function will go to infinity.
2. As [tex]\( x \)[/tex] approaches negative infinity ([tex]\( x \rightarrow -\infty \)[/tex]):
- [tex]\( 3^x \)[/tex] approaches 0 because any number raised to a negative power decreases towards zero.
- So, [tex]\( g(x) = 3^x + 4 \)[/tex] approaches [tex]\( 0 + 4 \)[/tex].
Hence, as [tex]\( x \)[/tex] approaches negative infinity, [tex]\( g(x) \)[/tex] approaches 4. Thus, the horizontal asymptote is:
[tex]\[ y = 4 \][/tex]
### Conclusion
The [tex]$y$[/tex]-intercept is [tex]\( (0, 5) \)[/tex] and the horizontal asymptote is [tex]\( y = 4 \)[/tex].
Thus, the correct multiple-choice answer is:
[tex]\[ (0, 5); y = 4 \][/tex]
Your participation means a lot to us. Keep sharing information and solutions. This community grows thanks to the amazing contributions from members like you. Find clear answers at IDNLearn.com. Thanks for stopping by, and come back for more reliable solutions.